2021
DOI: 10.1016/j.cell.2021.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A selective sweep in the Spike gene has driven SARS-CoV-2 human adaptation

Abstract: The COVID-19 pandemic underscores the need to understand better animal-to-human transmission of coronaviruses and adaptive evolution within new hosts. We scanned over 182,000 SARS-CoV-2 genomes for selective sweep signatures and found a distinct footprint of positive selection located around a non-synonymous change (A1114G; T372A) within the Spike protein receptor-binding domain (RBD), predicted to remove glycosylation and increase binding to human ACE2 (hACE2), the cellular receptor. This change is present in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 79 publications
5
67
0
Order By: Relevance
“…Through comparisons with the closely related bat RaTG13 and pangolin PCoV_GX coronaviruses, we further supported our previous proposal that tight RBD–ACE2 binding and efficient RBD “down” to “up” conformational transition are both required for SARS-CoV-2 to efficiently infect and transmit among humans 5 . While this paper was under preparation for submission, Kang et al reported a scanning over 182,000 SARS-CoV-2 genomes for selective sweep signatures and the identification of the same T372A change 9 . They showed that the A372T reversion mutation resulted in decreased viral replication in human lung cells and proved a decreased binding of the A372T mutant S glycoprotein to ACE2 in an ELISA-based binding assay 9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Through comparisons with the closely related bat RaTG13 and pangolin PCoV_GX coronaviruses, we further supported our previous proposal that tight RBD–ACE2 binding and efficient RBD “down” to “up” conformational transition are both required for SARS-CoV-2 to efficiently infect and transmit among humans 5 . While this paper was under preparation for submission, Kang et al reported a scanning over 182,000 SARS-CoV-2 genomes for selective sweep signatures and the identification of the same T372A change 9 . They showed that the A372T reversion mutation resulted in decreased viral replication in human lung cells and proved a decreased binding of the A372T mutant S glycoprotein to ACE2 in an ELISA-based binding assay 9 .…”
mentioning
confidence: 99%
“…While this paper was under preparation for submission, Kang et al reported a scanning over 182,000 SARS-CoV-2 genomes for selective sweep signatures and the identification of the same T372A change 9 . They showed that the A372T reversion mutation resulted in decreased viral replication in human lung cells and proved a decreased binding of the A372T mutant S glycoprotein to ACE2 in an ELISA-based binding assay 9 . The presence of the N370-linked glycans favoring the SARS-CoV-2 S glycoprotein to be in the closed state has also been proposed by Harbison et al 10 .…”
mentioning
confidence: 99%
“…Nevertheless, we provide population study evidence for the hypothesis that combines a founder effect with selection. We hypothesize that G614 predominance over D614 is an example of selective sweep in a viral population (Kang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kang et al suggests that a mutation in the receptor-binding domain of the SARS-CoV-2 virus' spike domain is largely responsible for the emergence of the novel coronavirus from sarbecoviruses, a subgenus of coronaviruses. This mutation, a substitution of threonine (T372) in the studied sarbecoviruses to alanine (A372) in SARS-CoV-2, allows SARS-CoV-2 to more easily replicate in human lung cells [63].…”
Section: Proteomics To Monitor Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2) Mutation Ratesmentioning
confidence: 99%